Fast automatic segmentation of thalamic nuclei from MP2RAGE acquisition at 7 Tesla. Issue 5 (3rd December 2020) - Datta, Ritobrato; Bacchus, Micky K.; Kumar, Dushyant; Elliott, Mark A.; Rao, Aditya; Dolui, Sudipto; Reddy, Ravinder; Banwell, Brenda L.; Saranathan, Manojkumar
Abstract : Purpose: Thalamic nuclei are largely invisible in conventional MRI due to poor contrast. Thalamus Optimized Multi‐Atlas Segmentation (THOMAS) provides automatic segmentation of 12 thalamic nuclei using white‐matter‐nulled (WMn) Magnetization Prepared Rapid Gradient Echo (MPRAGE) sequence at 7T, but increases overall scan duration. Routinely acquired, bias‐corrected Magnetization Prepared 2 Rapid Gradient Echo (MP2RAGE) sequence yields superior tissue contrast and quantitative T1 maps. Application of THOMAS to MP2RAGE has been investigated in this study. Methods: Eight healthy volunteers and five pediatric‐onset multiple sclerosis patients were recruited at Children's Hospital of Philadelphia and scanned at Siemens 7T with WMn‐MPRAGE and multi‐echo‐MP2RAGE (ME‐MP2RAGE) sequences. White‐matter‐nulled contrast was synthesized (MP2‐SYN) from T1 maps from ME‐MP2RAGE sequence. Thalamic nuclei were segmented using THOMAS joint label fusion algorithm from WMn‐MPRAGE and MP2‐SYN datasets. THOMAS pipeline was modified to use majority voting to segment bias corrected T1‐weighted uniform (MP2‐UNI) images. Thalamic nuclei from MP2‐SYN and MP2‐UNI images were evaluated against corresponding nuclei obtained from WMn‐MPRAGE images using dice coefficients, volume similarity indices (VSIs) and distance between centroids. Results: For MP2‐SYN, dice > 0.85 and VSI > 0.95 was achieved for five larger nuclei and dice > 0.6 and VSI > 0.7 was achieved for seven smaller nuclei. The dice and VSI were slightly higher, whereas the distance between centroids were smaller for MP2‐SYN compared to MP2‐UNI, indicating improved performance using the MP2‐SYN image. Conclusions: THOMAS algorithm can successfully segment thalamic nuclei in MP2RAGE images with essentially equivalent quality as WMn‐MPRAGE, widening its applicability in studies focused on thalamic involvement in aging and disease.